An ignored player in internationalisation: why and how does a Chinese regional university internationalise?. Issue 6 (2nd November 2021) - Xi, Xi; Rowlands, Kate E.
ABSTRACT: Most scholarly work on internationalisation in Chinese higher education institutions has been conducted on top-level universities but prior research does not necessarily apply to regional universities that are pursuing a strategy of internationalisation and recruiting international students. This research has selected a Chinese regional university as a case study and has investigated its rationale for and practices in implementing internationalisation. Data were collected primarily through the university's internal documents and 18 semi-structured interviews with university senior and middle managers. Results show that the university is motivated by quantitative indicators that relate to internationalisation in the China University Subject Rankings, which has determined the university's long-term and short-term financial resources, reputation and development opportunities. This instrumental approach to internationalisation has resulted in changes and challenges in the university's management and academic practices, and has indicated the debate of the good and bad of a strong government role in higher education internationalisation.